Analysis of Acceptance Factor in Education Technology Industry: Case Study of Aku Pintar - Sofian Lusa; Lutvianto Pebri Handoko; Prasetya Gilang Nuswantara (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
This research was motivated by the high number of wrong majors experienced by students in Indonesia. Along with the development of technology and because the ongoing COVID-19 pandemic has accelerated the “New Normal” in the field of education, it has now Edtech reached the stage of helping students in choosing a major according to their potential and talent interests. To improve the accuracy and ease of students finding majors according to their potential and talent interests, we would find out the factors that influence the acceptance of EdTech applications in selecting majors with a case study of the Aku Pintar application. However, there were various unknown factors regarding the level of achievement and acceptance of Majoring Test users in the Aku Pintar application. Based on this, this study wanted to identify the factors of acceptance of the major’s selection test in the Aku Pintar application. This study used the information success model which had been modified by adding variables from previous research recommendations. The variables used are information quality, system quality, service quality, user satisfaction, intention to use, and net benefit. The data collection method used an online survey via Google Forms. This research used a data analysis method from smartPLS. The results of the analysis showed that the factors that influence the success of the implementation of the major selection test in the Aku Pintar application were information quality, service quality, intention to use, user satisfaction, and net benefits.